Hurdles to herd immunity: Distrust of government and vaccine refusal in the US, 2002–2003. Issue 34 (25th July 2016) - Lee, Charlotte; Whetten, Kathryn; Omer, Saad; Pan, William; Salmon, Daniel
Highlights: Vaccine beliefs and behaviors of parents who distrust the government are analyzed. Distrusting parents have higher odds of seeking out CAM practitioners. Distrusting parents have higher odds of distrusting HCP's vaccine advice. Distrust in government is associated with low trust in govt. vaccine information. Public health communication may be less effective among low trust populations. Abstract: High rates of nonmedical exemptions (NMEs) from required childhood vaccinations have contributed to outbreaks of vaccine-preventable diseases, such as measles and pertussis. Understanding the parental decision to obtain an NME could help health professionals and public health programs improve vaccination rates in areas with high vaccine refusal. Using a 2002–2003 multi-state survey of parents of school age children ( ​n = 2445), this study found that parental distrust of the government and of healthcare providers is a significant factor related to a number of vaccine-related beliefs and behaviors. The odds that parents who distrust the government have seen a complementary/alternative medicine (CAM) provider were 2.11 times greater than those of parents who trust the government (70.1% vs 52.6%; OR, 2.11; 95% CI, 1.59–2.84; P < 0.01). Parents who distrust the government had increased odds of trusting vaccine information from CAM providers compared to trusting parents (57.9% vs 46.3%; OR, 1.53; 95% CI, 1.16–2.01; P < 0.01). Parents who distrust the government also had increased odds of distrusting vaccine information acquired at their healthcare providers' offices (12.6% vs 4.7%; OR, 2.64; 95% CI, 1.64–4.24; P < 0.01). Distrustful parents had increased odds of thinking government sources of information about vaccines were unreliable, categorizing the CDC, the Food and Drug Administration (FDA), or local and state health departments as poor or very poor sources (distrust government vs trust government: 25.2% vs 11.7%; OR, 2.39; 95% CI, 1.70–3.36; P < 0.01; distrust healthcare providers vs trust healthcare providers: 24.4% vs 11.4%; OR, 2.44; 95% CI, 1.75–3.38; P < 0.01). These findings indicate that distrustful parent populations may need to be reached through modalities outside of traditional government and healthcare provider communications. Research into new and more effective techniques for delivering pro-vaccine messages is warranted.